(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The aim of this study is to reveal the enhancement of wear resistance of AISI M35 tool steel by cryogenic treatment and Heat treatment by observing their tool life in terms of cutting length and surface roughness value obtained. Cryogenic treatment is often referred as cryo treatment, is an add-on process to the conventional heat treatment. In the experimentation process we have made two single point cutting which have undergone through heat treadment and cryogenic treatement. Those two tools we have fitted on standard all gear lathe machine. On Lathe machine we have conducted experimentation process for tool life keeping Speed (N), Feed (F), and Depth of Cut (D) as a input process parameters and tool life in terms of Cutting length and roughness value as a output parameter. Along with various angles and faces of tool the tool nose radios plays a very important role in producing good surface finish on component. Hence effect of this radius also has studied in this experimentation. Considering the length of paper we have not included microstructural details of material gone under processes.